2015
DOI: 10.5424/fs/2015242-07263
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the environmental control of leaf senescence of four Quercus species coexisting in a Mediterranean environment

Abstract: Aims of study: Our aim is to check the effect of different environmental factors on the leaf senescence of four Quercus species with different leaf longevities, to help us better understand the implications of climate change on leaf demography.Area of study: The study was carried out in two sites of the province of Salamanca (central-western Spain), both sites showing differences in their temperatures and soil water availability.Material and Methods: Over four years (2007)(2008)(2009)(2010) we monitored the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(64 reference statements)
1
1
0
Order By: Relevance
“…As shown in these studies, winter and spring precipitation exerted a large positive effect on treering growth due to the replenishment of soil water reserves before the onset of the favorable growing season (Costa et al 2001;Jovellar et al 2010;Costa et al 2016;Zribi et al 2016;Leite et al 2019). In our study site, Q. suber showed the latest leaf emergence of all coexisting Quercus species, with budbreak and emergence of the new leaf cohort occurring between the end of May and the beginning of June (del Río et al 2015). However, in relation to other studies where temperature has been found to have an insignificant or negative effect over cork or ring growth (Caritat et al 1996;Costa et al 2001;Zribi et al 2016), in our study site, the mean and minimum temperatures during winter and/or spring and the mean and maximum temperatures during September exerted a positive influence on tree growth.…”
Section: Regeneration Dynamics Of Quercus Speciessupporting
confidence: 53%
“…As shown in these studies, winter and spring precipitation exerted a large positive effect on treering growth due to the replenishment of soil water reserves before the onset of the favorable growing season (Costa et al 2001;Jovellar et al 2010;Costa et al 2016;Zribi et al 2016;Leite et al 2019). In our study site, Q. suber showed the latest leaf emergence of all coexisting Quercus species, with budbreak and emergence of the new leaf cohort occurring between the end of May and the beginning of June (del Río et al 2015). However, in relation to other studies where temperature has been found to have an insignificant or negative effect over cork or ring growth (Caritat et al 1996;Costa et al 2001;Zribi et al 2016), in our study site, the mean and minimum temperatures during winter and/or spring and the mean and maximum temperatures during September exerted a positive influence on tree growth.…”
Section: Regeneration Dynamics Of Quercus Speciessupporting
confidence: 53%
“…S1), but it is also directly involved in improving soil water retention in abandoned cultivars, especially in soils with high sand content (Rawls ). In our study site, Q. suber showed the latest leaf emergence of all coexisting Quercus species, with budbreak and emergence of the new leaf cohort occurring between the end of May and the beginning of June (del Río et al 2015). However, in relation to other studies where temperature has been found to have an insigni cant or negative effect over cork or ring growth (Caritat et al 1996, Costa et al 2001, Zribi et al 2016, in our study site, the mean and minimum temperatures during winter and/or spring and the mean and maximum temperatures during September exerted a positive in uence on tree growth.…”
Section: Resultsmentioning
confidence: 86%
“…The positive effect of autumn temperature on leaf senescence was also confirmed in Mediterranean tree species. Del Río García et al (2015) reported delayed leaf senescence due to warmer autumn conditions in four coexisting Mediterranean Quercus species. This may lead to smaller differences in the length of productive leaf life of deciduous species compared to evergreen species, thereby improving the competitive ability of the former (del Río García et al, 2015).…”
Section: Effect Of Weather Conditions On Leaf Phenologymentioning
confidence: 99%